2022
DOI: 10.3390/jpm12071154
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a miRNA-Based Nomogram Model to Predict the Prognosis of Endometrial Cancer

Abstract: Objective: To investigate the differential expression of microRNA (miRNA) in patients with endometrial cancer and its relationship with prognosis and survival. Method: We used The Cancer Genome Atlas (TCGA) database to analyze differentially expressed miRNAs in endometrial cancer tissues and adjacent normal tissues. In addition, we successfully screened out key microRNAs to build nomogram models for predicting prognosis and we performed survival analysis on the key miRNAs as well. Result: We identified 187 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…NF-κB, RelA (a subunit of NF-κB) and CEBPB are both key regulators in inflammation (Zahid et al, 2020;Zhao et al, 2020). MiRNAs can regulate various target genes in numerous biological processes and diseases, such as endometrial cancer (Ni et al, 2022). It has been reported that miR-181 family present a central role in vascular inflammation (Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB, RelA (a subunit of NF-κB) and CEBPB are both key regulators in inflammation (Zahid et al, 2020;Zhao et al, 2020). MiRNAs can regulate various target genes in numerous biological processes and diseases, such as endometrial cancer (Ni et al, 2022). It has been reported that miR-181 family present a central role in vascular inflammation (Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies use gene set, RNA set model to predict the occurrence of disease and the prognosis of patients. Through integrating 12 differentially expressed miRNAs, it may affect the proliferation, invasion and metastasis of endometrial cancer, and then predict the prognosis of patients ( 37 ). Likewise, as an important component of the ferroptosis-mediated metabolic change gene set, IMPDH1 is found to be a risk factor in the risk score model for predicting OS of HCC patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies have reported prognostic prediction models for UCEC. Ni et al constructed a prognostic model composed of 12 miRNAs for UCEC, which can accurately predict the survival of UCEC [ 58 ]. Using redox-related genes, Geng et al developed a clinical outcome prognostic model [ 59 ].…”
Section: Discussionmentioning
confidence: 99%